Static pile-soil-pile interaction in offshore pile groups - Chaudhry, A; A. R. Chaudhry (1994)
This thesis is a theoretical study, using both finite element and boundary element methods, of the behaviour of single-piles and pile groups under vertical and lateral loading. It offers an improved understanding of the soil-structure interaction that occurs in pile groups, particularly closely spaced piles subjected to lateral loads. The potential of a two- dimensional idealisation of what is a three-dimensional problem is demonstrated by achieving real insight into the complex nature of pile-soil and pile-soil-pile interaction in pile groups. A new load transfer mechanism is presented for a rigid, axially loaded vertical pile. From this an improvement is then derived to the analytical solution for pile head settlement given by Randolph and Wroth (1978). The improved mechanism has the further merit that it can be applied also to solutions for flexible piles and pile groups. The improved analytical solution is further adapted in the development of two correcting layers specifically for vertically loaded piles to model infinite boundaries in the finite element model. The correcting layers help in establishing superiority of the finite element method over the boundary element method. To model pile-soil interaction, a purely cohesive interface element is developed and then validated by performing various two-dimensional test problems, including stability analysis of flat surface footings. Footing-soil interface tension is successfully modelled in this way - an outcome that entails a significant modification to the Hansen (1970) bearing capacity solution. Stability analysis is also carried out of conical footings using a three-dimensional finite element model: the results help to explain the applicability of the existing bearing capacity theories to conical footings. The ultimate lateral soil reaction is determined and various pile loading stages are investigated through parametric studies. Study of the stage immediately following pile installation (i.e. the consolidation stage) highlights the need to develop an effective stress analysis for laterally loaded piles. Pile-soil interaction is studied using the cohesive interface element presented earlier, which proves to be quite successful in smoothing out the stress discontinuities around the pile. A new material model for frictional soils is presented, and validated by using it to model an extension test: it captures well post-peak behaviour and takes care of the effects of dilation on the response of laterally loaded piles. Finally, mechanisms of interaction in closely spaced pile groups are studied. Simple analytical expressions are derived which quantify the effects of interaction. A new method of analysis is presented for single-piles and pile groups which offers a considerable degree of reliability without having to do either impossibly expensive full scale field tests or prohibitively expensive full three-dimensional analysis using the currently available computers.